Stress intensity factors for a Brazilian disc with a central crack subjected to compression. (March 2017) - Tang, S.B.
Abstract: A closed-form solution for stress intensity factors (SIFs) derived using the weight function method is developed to study the effects of crack length, loading type and friction on center-cracked Brazilian disc (CCBD) specimens. The proposed method is suitable for both opening- and closing-mode cracks. The effects of loading angle, friction coefficient and loading type (concentrated load, partially distributed pressure and confining pressure) on the SIFs are studied. The results are compared to available finite element results. It is found that the mode I SIF decreases as the relative crack length, partially distributed pressure angle and confining pressure increase. An increase in friction causes a decrease in the mode II SIF when the crack surfaces are in contact with each other. The critical crack inclination angles of both pure mode II loading ( K I =0) and crack sticking ( K II =0) decrease as the relative crack length and confining pressure increase. The critical crack inclination angle of crack sticking also decreases with increasing friction. When sticking conditions arise on the crack surfaces, the singular stress at the crack tip disappears. Confining pressure enhances the likelihood of sticking behavior in the crack. Highlights: A closed-form solution for SIF is developed for center-cracked Brazilian disc specimen. The effect of friction coefficient on the SIFs is studied. The critical crack inclination angles of pure mode II loading are discussed. The angle for crack sticking decreases with increasing friction. Confining pressure enhances the likelihood of sticking behavior in the crack.